Quantification of Complaint and Compensation Cases by Introducing a Danish Translated and Cross-Cultural Adapted Edition of the Healthcare Complaints Analysis Tool - Morsø L; Walløe S; Birkeland S; Mikkelsen KL; Gudex C; Bogh SB (Dove Medical Press, 2021)
Lars Morsø,1 Sisse Walløe,1 Søren Birkeland,1 Kim Lyngby Mikkelsen,2 Claire Gudex,1 Søren Bie Bogh1 1OPEN – Open Patient Data Explorative Network, Odense University Hospital, Department of Clinical Research, University of Southern Denmark, Odense C, DK-5000, Denmark; 2Danish Patient Compensation Association, Copenhagen V, DK-1560, DenmarkCorrespondence: Lars MorsøDepartment of Clinical Medicine (OPEN), University of Southern Denmark, J. B. Winsløws Vej 9a, 3rd Floor, Odense C, DK-5000, DenmarkTel +45 21 82 60 04Email lars.morsoe@rsyd.dkPurpose: The study aimed to translate and cross-culturally adapt the English version of the HCAT to produce a Danish HCAT version and to test the Danish version’s reliability.Methods: We used best-practice guidelines for linguistic translations and cultural adaptations. For cross-cultural adaptation, we conducted forward and back translation followed by expert committee review. Subsequently, two researchers assessed 140 complaint cases to test intra- and inter-rater reliability of the Danish HCAT version. We used descriptive statistics for distributions and tested for differences between English and Danish editions Intra- and inter-rater reliability used Gwet’s AC1 statistics, applying quadratic weights to assign more weight to large discrepancies.Results: The back translations showed both semantic and conceptual differences, and the expert committee thus discussed the meaning of the wording in the HCAT guide and coding form to ensure that the Danish version would be conceptually similar to the English version but also culturally appropriate for Danish settings. There was discussion about how to use the coding form to graduate problem severity, and this led to some altered wording. Pilot testing revealed the need for two new categories of “hospital-acquired infection” and “involvement of patients’ relatives”. The problem categories of the HCAT-DK showed “substantial” intra- and inter-rater reliability (0.79, and 0.79 to 0.85). In addition, there was a “substantial” agreement (0.70 to 0.73) between the original HCAT and the HCAT-DK version.Conclusion: The study translated and cross-culturally adapted the English HCAT version to produce a Danish HCAT version. Cultural and conceptual differences led to adjustments and to addition of two extra items in the HCAT-DK. The Danish version showed “substantial” intra- and inter-rater reliability and is considered suitable for coding complaint and compensation cases in Danish health care.Keywords: HCAT, translation, cross-cultural adaption, reliability, HCAT-DK